Metodologi Identifikasi Golongan Dan Daerah Miskin : Suatu Tinjauan Dan Alternatif - [Tidak Terdaftar] (Grasindo, 1995)
Metodologi Identifikasi Golongan Dan Daerah Miskin : Suatu Tinjauan Dan Alternatif